Of Horses and Carts: Theories of Indefeasibility and Category Errors in the Torrens System - LOW, Kelvin F. K. (Institutional Knowledge at Singapore Management University, 2010)
The essays collected in this volume are drawn from multiple jurisdictions and cover a broad range of legal issues – demonstrating both Michael Bryan's breadth of scholarly interests and the reach of his work. Of the many subjects that have engaged his interest, Bryan's knowledge and expertise in equity is unquestionable, having written dozens of articles on the subject of equity and trusts and being invited to contribute to the seminal Australian text on the law of trusts. One fascinating area in this wide landscape of equity is how equitable principles apply and operate in the context of Torrens land registration. For some years now, Bryan has been teaching this difficult subject in a course entitled ‘Equity in Real Property Law’ for the Melbourne Law Masters programme. However, those of us who have not had the benefit of attending Bryan's course may glimpse his insight into the subject only through his published work. His first on this subject was originally published in the University of Queensland Law Journal before it was reprinted with an expanded introduction in one of the many Festschriften honouring the late Peter Birks – Structure and Justification in Private Law. In that article, ‘Recipient Liability under the Torrens System: Some Category Errors’, Bryan lamented that, as it analyses what some might consider ‘a narrowly domestic issue of Australian law … it might have disappointed Birks, who was ever the opponent of legal nationalism’.